Chloride-dependent conformational changes in the GlyT1 glycine transporter - Zhang, Yuan-Wei (Proc Natl Acad Sci U S A, 2021)
The human GlyT1 glycine transporter requires chloride for its function. However, the mechanism by which Cl(−) exerts its influence is unknown. To examine the role that Cl(−) plays in the transport cycle, we measured the effect of Cl(−) on both glycine binding and conformational changes. The ability of glycine to displace the high-affinity radioligand [(3)H]CHIBA-3007 required Na(+) and was potentiated over 1,000-fold by Cl(−). We generated GlyT1b mutants containing reactive cysteine residues in either the extracellular or cytoplasmic permeation pathways and measured changes in the reactivity of those cysteine residues as indicators of conformational changes in response to ions and substrate. Na(+) increased accessibility in the extracellular pathway and decreased it in the cytoplasmic pathway, consistent with stabilizing an outward-open conformation as observed in other members of this transporter family. In the presence of Na(+), both glycine and Cl(−) independently shifted the conformation of GlyT1b toward an outward-closed conformation. Together, Na(+), glycine, and Cl(−) stabilized an inward-open conformation of GlyT1b. We then examined whether Cl(−) acts by interacting with a conserved glutamine to allow formation of an ion pair that stabilizes the closed state of the extracellular pathway. Molecular dynamics simulations of a GlyT1 homolog indicated that this ion pair is formed more frequently as that pathway closes. Mutation of the glutamine blocked the effect of Cl(−), and substituting it with glutamate or lysine resulted in outward- or inward-facing transporter conformations, respectively. These results provide an unexpected insight into the role of Cl(−) in this family of transporters.